2021
DOI: 10.1021/acs.langmuir.1c02253
|View full text |Cite
|
Sign up to set email alerts
|

MOF@COF Heterostructure Hybrid for Dual-Mode Photoelectrochemical–Electrochemical HIV-1 DNA Sensing

Abstract: We developed a novel metal–organic framework (MOF)@covalent–organic framework (COF) hybrid with a hierarchical nanostructure and excellent photoactivity, which further acted as the bifunctional platform of a dual-mode photoelectrochemical (PEC) and electrochemical (EC) biosensor for detecting HIV-1 DNA via immobilizing the HIV-1 DNA probe. First, the presynthesized Cu-MOF nanoellipsoids were used as the template for the in situ growth of the COF network, which was synthesized using copper-phthalocyanine tetra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…COFs can be used as structural materials to adsorb oligonucleotides and their further use as DNA probes for the development of genosensors. A hybrid MOF/COF nanocomposite material was developed by Miao Du's research group [119] (Figure 7). The developed nanocomposite material has been used on a label free genosensor for HIV-1 DNA probe.…”
Section: Genosensorsmentioning
confidence: 99%
“…COFs can be used as structural materials to adsorb oligonucleotides and their further use as DNA probes for the development of genosensors. A hybrid MOF/COF nanocomposite material was developed by Miao Du's research group [119] (Figure 7). The developed nanocomposite material has been used on a label free genosensor for HIV-1 DNA probe.…”
Section: Genosensorsmentioning
confidence: 99%
“…Timeline of the representative studies on MOF/COF composites (bottom). [34][35][36][37][38][39][40][41][42][43] Figures reprinted with permissions from ref. 34, 35, 38, 39, 42 and 43. This journal is © The Royal Society of Chemistry 2022 MOF/COF hybrid structures have been recently synthesized as core-shell structures (MOF@COF or COF@MOF), heterostructures, and composites.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid materials constructed from both MOFs and COFs, known as MOFs@COFs, combine the advantages both materials, meaning that they are widely used in applications including catalysis, gas separation, and sensing. [24][25][26] Fu et al 27 reported the COFs-300@ZIF-8 composite, which showed the highest separation selectivity performance for H 2 /CO 2 gas mixtures. Lan et al 28 provided an integrated porous NH 2 -UiO-66/TpPa-1-COFs hybrid with good photocatalytic H 2 evolution under visible light.…”
Section: Introductionmentioning
confidence: 99%